Does the use of bedside ultrasonography reduce emergency department length of stay for patients with renal colic?: a pilot study - Yong Hoon Park; Ru Bi Jung; Young Geun Lee; Chong Kun Hong; Jung-Hwan Ahn; Tae Yong Shin; Young Sik Kim; Young Rock Ha (Clinical and Experimental Emergency Medicine, 2016)
Objective The aim of this study was to evaluate the effect of adding bedside ultrasonography to the diagnostic algorithm for nephrolithiasis on emergency department (ED) length of stay. Methods A prospective, randomized, controlled pilot study was conducted from October 2014 to December 2014 with patients with acute flank pain. In the non-ultrasonography group (NUSG), non-contrast computed tomography was selected based on clinical features and hematuria in the urinalysis. In the ultrasonography group (USG), non-contrast computed tomography was selected based on clinical features and hydronephrosis on bedside ultrasonography. The primary outcome was ED length of stay. The secondary outcomes were radiation exposure, amount of analgesics, proportion of patients with diseases other than ureteral calculus, and proportion of patients with unexpected ED revisits within 7 days from the index visit. Results A total of 103 patients were enrolled (NUSG, 51; USG, 52). The ED length of stay for the USG (89.0 minutes) was significantly shorter than that for the NUSG (163.0 minutes, P<0.001). There were no significant differences between the two groups in the radiation exposure dose (5.29 and 5.08 mSv, respectively; P=0.392), amount of analgesics (P=0.341), proportion of patients with diseases other than ureteral calculus (13.0% and 6.8%, respectively; P=0.486), and proportion of patients with unexpected ED revisits within 7 days from the index visit (7.8% and 9.6%, respectively; P=1.000). Conclusion The use of early bedside ultrasonography for patients with acute flank pain could reduce the ED length of stay without increasing unexpected ED revisits.